2021
DOI: 10.1002/cnr2.1522
|View full text |Cite
|
Sign up to set email alerts
|

Identification of PSMD14 as a potential novel prognosis biomarker and therapeutic target for osteosarcoma

Abstract: Background: Osteosarcoma is the most common primary bone tumor. The survival rate of osteosarcoma patients has not significantly increased in the past decades.Uncovering the mechanisms of malignancy, progression, and metastasis will shed light on the development of new therapeutic targets and treatment for osteosarcoma. Aim:The aim of this study is to identify potential osteosarcoma biomarker and/or therapeutic targets by using integrated bioinformatics analysis. Methods and results:We utilized existing gene e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 51 publications
1
6
0
2
Order By: Relevance
“…Similarly, high expression of PSMD14 is associated with a worse prognosis in multiple myeloma, esophageal, ovarian, breast cancer and osteosarcoma. Although expression is associated with prognosis and occasionally with advanced cancer features in these studies, correction of the prognostic relevance of PSMD14 for potential confounders was not described (Lv et al 2019;Luo et al 2017;Song et al 2017;Sun et al 2021;Gong and Wei 2021). In accordance with our results, Zhang et al revealed that PSMD14 is associated with OS and DFS in lung adenocarcinoma.…”
Section: Secondary Dataset (Tma)-analysis Of Psmd14 Protein Expressionsupporting
confidence: 82%
“…Similarly, high expression of PSMD14 is associated with a worse prognosis in multiple myeloma, esophageal, ovarian, breast cancer and osteosarcoma. Although expression is associated with prognosis and occasionally with advanced cancer features in these studies, correction of the prognostic relevance of PSMD14 for potential confounders was not described (Lv et al 2019;Luo et al 2017;Song et al 2017;Sun et al 2021;Gong and Wei 2021). In accordance with our results, Zhang et al revealed that PSMD14 is associated with OS and DFS in lung adenocarcinoma.…”
Section: Secondary Dataset (Tma)-analysis Of Psmd14 Protein Expressionsupporting
confidence: 82%
“…The mechanism underlying the action of PSMD14 involves binding to a C-terminal isopeptide substrate to remove a polyubiquitin segment, thus promoting the transport of the substrate and degradation of the CP. 20 Although the proteasome system cannot degrade aggregated proteins, intriguingly, PSMD14 appears to exert a positive impact on autophagy function. 21 The cellular autophagy pathway is closely related to tumorigenesis, infection, neurodegenerative diseases and other diseases, whereas inhibition of cellular endocrine autophagy can delay the progression of these diseases.…”
Section: Discussionmentioning
confidence: 99%
“…PSMD14 is a kind of deubiquitinating enzymes (DUBs) and was reported to be connected with tumor progression and poor prognosis in many types of cancer including neck squamous cell carcinoma ( 38 ), non-small cell lung cancer ( 39 ), ovarian cancer ( 40 ), and hepatocellular carcinoma ( 41 ). Gong considered that a high expression of PSMD14 in tumor cells may lead to aging or failure of CD8+ T cells, which may explain the positive correlation between high expression of CD8+ T cells and PSMD14 and poor prognosis in osteosarcoma ( 42 ). PSMB5 is a member of the PSMB family and ubiquitin-proteasome system, which was demonstrated to play important roles in tumor progression and immune cell infiltration, especially in breast cancer.…”
Section: Discussionmentioning
confidence: 99%